Types and abundance of macro and micro-marine debris at Sebatik Island, Tawau, Sabah - Abentin Estim; Rafidah Sudirman (Borneo Marine Research Institute, 2017)
The amount of marine debris is increasing worldwide and has become a matter of serious concern. It is important to identify the nature of debris to understand the sources and to devise practically feasible methods for managing this problem. This study was carried out at Sebatik Island on the east coast of Sabah with the aim of examining the types and abundance of macro – and micro-debris. The observations covered a period of December 2015 – May 2016. Debris collected from different stations was compared. Transect line method was used to assess the stranded macro-marine debris (SMD). Evaluation of floating macro- debris (FMD) was done by surveys of the selected areas. Density separation technique was applied in order to extract the micro marine debris (MMD). Results showed 14 types of SMD and 9 types of FMD in the study areas. Three major types of SMD and FMD were discarded plastic, organic debris and plastic bottles. Four types of MMD recorded at the beach and mudflat areas were fragments, fiber, films and polystyrene. Based on the comparison between stations (S), S2 showed the highest abundance of SMD with 80 items m-2. Meanwhile, FMD at one location was as high as 94 items m-2. Station S3 has the highest of MMD with 22 items ml-1. Plastic formed (40%) of the SMD category whereas FMD constituted 42 % at the Sebatik Island. Small fragments and film were the most abundant of MMD (32 %). This study highlights the scale of the marine debris problem in Sebatik Island and calls for a comprehensive plan of action to protect the Island’s marine ecosystem services.